2012
DOI: 10.1088/1468-6996/13/4/043001
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical adaptive nanostructured PVD coatings for extreme tribological applications: the quest for nonequilibrium states and emergent behavior

Abstract: Adaptive wear-resistant coatings produced by physical vapor deposition (PVD) are a relatively new generation of coatings which are attracting attention in the development of nanostructured materials for extreme tribological applications. An excellent example of such extreme operating conditions is high performance machining of hard-to-cut materials. The adaptive characteristics of such coatings develop fully during interaction with the severe environment. Modern adaptive coatings could be regarded as hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 236 publications
(433 reference statements)
0
57
0
1
Order By: Relevance
“…Assuming that the tensor component satisfies, σ 33 = 0, σ 23 = σ 13 =0, σ 11 = σ 22 = σ, then Equation (1) becomes Equation (3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that the tensor component satisfies, σ 33 = 0, σ 23 = σ 13 =0, σ 11 = σ 22 = σ, then Equation (1) becomes Equation (3).…”
Section: Methodsmentioning
confidence: 99%
“…High hardness combined with the low thermal conductivity is mandatory for continuous dry cutting conditions associated with hard turning [1]. However, when the cutting environment becomes more complex, as in interrupted cutting conditions the coating layer must achieve improved multi-functionality [3]. Modern hard PVD (Physical vapor deposition) coatings mostly have a nano-crystalline columnar structure [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that there are two types of tribofilms that are formed on the frictional body as a result of structural modification and interaction with the environment: (1) super-ductile and lubricating films [12]; and (2) tribo-ceramics with thermal barrier properties and increased hardness and strength [10,24,26,27,[30][31][32][33][34][35][36][37][38][39]. Tribofilms (SS) of the first type (SS-I) are observed as a result of structural activation marked by an increase in the density of atomic defects at the surface.…”
Section: Thermodynamics Of Tribofilmsmentioning
confidence: 99%
“…Various features of tribofilms (or secondary structures, i.e., generated during friction) were intensively studied [6][7][8][9][10][11][12][13][14][15][16][17]. The tribofilms generated during friction can be divided into lubricating [6] and hard ceramic tribo-phases [7].…”
Section: Introductionmentioning
confidence: 99%